Transforming the equation cot ⁡ x − cos ⁡ x = 0 into the form...

kolutastmr

kolutastmr

Answered

2022-07-16

Transforming the equation cot x cos x = 0 into the form cos x ( 1 sin x ) = 0

Answer & Explanation

Asdrubali2r

Asdrubali2r

Expert

2022-07-17Added 14 answers

cot ( X ) cos ( X ) = 0 cos X sin X cos X = 0 cos X ( 1 sin X 1 ) = 0
cos X ( 1 sin X ) sin X = 0 cos X ( 1 sin X ) = 0 sin X = 0
This applies when sin X 0. If it is zero, then cot X = so the equation is not satisfied

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?